Hubungan Stres dengan Kejadian Burnout pada Mahasiswa Fakultas Kedokteran Universitas Ahmad Dahlan: Penelitian - Shifa, Siti Ma'rifatus; Desvita, Widea Rossi; Qomariyah, Nurul (Cermin Dunia Kedokteran, 2026)
Background: Burnout can occur in individuals exposed to intense and prolonged repetitive stress. The various activities of medical students require a change in learning style from high school to college, which has the potential to cause stress. This study aims to determine the relationship between stress and burnout among students of the Faculty of Medicine, Universitas Ahmad Dahlan. Methods: The research was conducted quantitatively with a cross-sectional design. The sample was 60 students in the 3rd, 5th, and 7th semesters chosen with a with random stratified sampling technique. Results: Most of the students (80.0%) had moderate stress levels and most of the burnout levels were low (45.0%). Bivariate analysis obtained p value < 0.001 and r value = 0.641 (r > 0). In addition, an R-squared of 0.411 was obtained, which shows that the stress level makes a statistical contribution of 41.1% to the variation in burnout, and the remaining 58.9% could be influenced by other factors. Conclusion: There was a significant positive relationship between stress and burnout among students of the Faculty Medicine, Universitas Ahmad Dahlan.